Frontiers of peace economics and peace science - Chatterji, Manas, 1937-; Bo, Chen; Misra, R. P. 1930- (Emerald, 2011)
Over the last three decades, a considerable amount of work has been conducted in the field of peace studies, conflict management, peace science in economics, sociology, anthropology and management. This volume presents up-to-date, cutting-edge research by respected scholars with an emphasis on theoretical and mathematical constructs in the area of peace economics & peace science.
Includes indexes.
Keywords: Peace -- Economic aspects.; Peace-building -- Economic aspects.; elektronické knihy; electronic books